Development Of An IoT Environmental Information System For Users Of GPS-Based Public Transport - Mar, Hee Sheng (Universiti Sains Malaysia, 2018)
The Internet-of-Things (IoT) brings a development potential to transform the communities into Smart Cities with the idea of incorporating data collection and services sharing. It brings a lot of benefits including lowering levels of pollution, real-time weatherforecasting, improving traffic, building up energy efficiency, and a better overall quality of life for the future citizen. This research work proposes a mobile environmental sensing platform for city information collection and condition monitoring by feeding the data to a cloud computing system. To develop the system, the air quality sensor, temperature and humidity sensors and geolocation module are designed and interfaced with a Raspberry Pi 3. After that, environmental parameters are collected, stored in PhpMyadmin local database and uploaded to ThingSpeak cloud database in real-time. Then, the data are pre-processed and visualized graphically for further data analyses and monitoring. A prototype field test has been carried out to investigate proper working of the developed system using the conventional static sensing and new mobile sensing. It is found that there is a 6.93% difference between the static and mobile sensing method, which is rather small. Overall, the development of the IoT environmental information system by using mobile sensing has been a success and able to facilitate environmental sensing and monitoring.